Altered Autophagy-Associated Genes Expression in T Cells of Oral Lichen Planus Correlated with Clinical Features - Ya-Qin Tan; Jing Zhang; Ge-Fei Du; Rui Lu; Guan-Ying Chen; Gang Zhou (Hindawi Limited, 2016)
Oral lichen planus (OLP) is a T cell-mediated inflammatory autoimmune disease. Autophagy has emerged as a fundamental trafficking event in mediating T cell response, which plays crucial roles in innate and adaptive immunity. The present study mainly investigated the mRNA expression of autophagy-associated genes in peripheral blood T cells of OLP patients and evaluated correlations between their expression and the clinical features of OLP. Five differentially expressed autophagy-associated genes were identified by autophagy array. Quantitative real-time RT-PCR results confirmed that IGF1 expression in the peripheral blood T cells of OLP patients was significantly higher than that in controls, especially in female and middle-aged (30-50 years old) OLP patients. In addition, ATG9B mRNA levels were significantly lower in nonerosive OLP patients. However, no significant differences were found in the expression of HGS, ESR1, and SNCA between OLP patients and controls. Taken together, dysregulation of T cell autophagy may be involved in immune response of OLP and may be correlated with clinical patterns.